Legitimate vs. illegitimate restrictions – a motivational and physiological approach investigating reactance processes - Sittenthaler, Sandra; Steindl, Christina; Jonas, Eva (Frontiers in Psychology, 2015)
Threats to our freedom are part of our daily social interactions. They are accompanied by an aversive state of motivational arousal, called reactance, which leads people to strive to reestablish their threatened freedom. This is especially the case if the threat seems to be illegitimate in nature. However, reactance theory suggests that reactance should also be aroused when people are exposed to legitimate freedom threats. In this article we first aim to show that both illegitimate and legitimate freedom threats evoke reactance. Second, we aim to extend past work on reactance by exploring the underlying process of experiencing a legitimate versus an illegitimate restriction. In the current study (N = 57) participants were restricted in an illegitimate (unexpected and inappropriate) or legitimate (unexpected but appropriate) way, or were not restricted at all. We assessed participants’ experience of reactance, their behavioral intentions to restore their freedom, their approach motivational states, as well as their physiological arousal (heart rate). Results indicated that when restricted in an illegitimate or a legitimate way, participants indicated the same amount of reactance as well as anger. However, when looking at people’s physiological reactions, important differences between illegitimate and legitimate restrictions become apparent. Illegitimate restrictions led to an immediate arousal, whereas legitimate restrictions led to a time delayed arousal. This suggests that illegitimate restrictions lead to a sudden increase in aversive arousal. Legitimate restrictions, however, seem to be associated with a more cognitive process in which people first need to structure their thoughts and reflect upon the situation before getting into the feeling of reactance in a physiologically arousing sense. Moreover a mediation analysis could show that behavioral intentions to regain one’s freedom result in positive and negative approach motivation. In sum we propose a combined